1993
DOI: 10.1002/dc.2840090303
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of cytologic specimens by flow cytometry

Abstract: Immunophenotyping by flow cytometry is well established as an ancillary technique in the diagnosis of hematopoietic neoplasms. However, flow cytometry is rarely performed on cytologic specimens because most cytologist are more comfortable with direct microscopy and believe that there is inadequate cellularity for analysis. Paradoxically, cytologic material is usually cell suspensions making it ideal for flow cytometry. In order to evaluate the usefulness of immunophenotyping cytologic specimens by flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 11 publications
0
36
1
Order By: Relevance
“…The accuracy of subclassifying lymphomas using cytomorphological and flow cytometric immunophenotyping has been demonstrated. [35][36][37] Sarcomas Sarcomas are usually characterized by a spindle cell appearance. Gastrointestinal stromal tumors and leiomyosarcomas are the most frequent sarcomas to metastasize to the liver.…”
Section: Diagnostic Dilemmasmentioning
confidence: 99%
“…The accuracy of subclassifying lymphomas using cytomorphological and flow cytometric immunophenotyping has been demonstrated. [35][36][37] Sarcomas Sarcomas are usually characterized by a spindle cell appearance. Gastrointestinal stromal tumors and leiomyosarcomas are the most frequent sarcomas to metastasize to the liver.…”
Section: Diagnostic Dilemmasmentioning
confidence: 99%
“…These include: flow cytometry with deoxyribonucleic acid (DNA) analysis [26][27][28] or immunocytometry [29]; electron microscopic examination [30,31]; and immunohistochemical studies [32][33][34]. The theory behind DNA analysis is that malignant cells will have abnormal numbers of chromosomes and, therefore, an abnormal amount of DNA.…”
Section: Cytology Of the Pleural Fluidmentioning
confidence: 99%
“…However, studies have shown that DNA analysis via flow cytometry is less sensitive than cytology [26,27], and also has more false positives than cytology [28]. Flow cytometry using immunocytometry can identify the cell lineage (T-or B-cells) and the clonality of a population of lymphocytes [29]. Therefore, this is a useful test when pleural lymphoma is suspected.…”
Section: Cytology Of the Pleural Fluidmentioning
confidence: 99%
“…7 The potential advantages of flow cytometry include the rapidity of analysis compared with immunohistochemistry, the ability to enrich for possible malignant cells via gating techniques in samples with mixed cell populations, and the simultaneous evaluation of multiple surface markers on each cell. In the past, limited sample volume, low cell counts, and the presence of cellular debris or reactive lymphocyte populations could lower the sensitivity of flow cytometry in recovering clonal lymphocyte populations.…”
mentioning
confidence: 99%